(untitled) (The Strategic Review for Southern Africa, 2020)
The paper discusses the relationship between the People's Republic of China and Angola in the 21st century in the broader context of Chinese economic activity in Africa. I discuss the effectiveness of the “Angola Model” of this relationship as a gateway for cooperation with Africa. The main research question is whether the “Angola Model” is an effective way to increase China's involvement in Africa and whether it has been applied to other countries on the continent? I hypothesise that the implementation of this model allows China to intensify economic cooperation with African countries because this model brings mutual benefits to partners. China gains access to energy resources, new markets and investment opportunities, while African states obtain loans, revenues from the sale of raw materials and assistance in infrastructure development. To some extent, the Angola Model also allows China to spread political influence, but the example of Angola shows that it has several limitations. China has implemented elements of economic cooperation characteristic of the Angola Model in many African countries.